The Effects of Movement in the Classroom - Carrie Jean Braniff (Networks: An Online Journal for Teacher Research, 2011)
After teaching and substitute teaching in various classrooms, I was determined to have a classroom full of movement and energy. In order to create an active classroom, I implemented several strategies that would help students work together, have opportunities for transitions and movement, and provide a reduced-stress environment. In order to study the influence of activity in the classroom, I did an action research study. I collected data, observation notes, and journal entries from the students during classroom activities. These journal entries the students included surveys that were completed at the beginning and end of the study. Collecting articles from journals and books was also part of my study. After much data collection I began to organize my information into themes around patterns that became evident during my observations. The themes that were evident included: movement affected classroom management, students were eager to move, movement impacted learning, the physical location of seatwork affected learning, movement impacted alertness and attention, and movement impacted nerves and well-being of the students. This study found that exercise in the classroom helped students to reach their potential. It also reduced stress for the students. Exercise has a valuable place in the classroom.